2017
DOI: 10.1504/ijric.2017.082299
|View full text |Cite
|
Sign up to set email alerts
|

The impact of technological innovation on SME's profitability in Nigeria

Abstract: Abstract:There is no doubt that new or improved product or process of production continues to create firm's competitive advantage over others in the market. This study examined the impact of research and development (R&D) expenditure, product and process innovations on small and medium enterprises (SMEs) performance in the manufacturing industry in Nigeria using a survey of 1,000 SMEs with a response rate of 52.1% in year 2009. The results with least squares method showed that R&D spending by the firms as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The results indicate that the technological innovation has a significant positive effect on the business performance of Latin American family SMEs. In addition, (Akinwale et al , 2017) examined the impact of research and development (R&D) expenditure, product and process innovations on SMEs performance in the manufacturing industry in Nigeria using a survey of 1,000 SMEs. Their results with the least squares method showed that R&D spending by the firms as well as product and process innovation has significant impacts on the firm's performance.…”
Section: Innovation and Performance In Small And Medium Enterprises: A Literature Reviewmentioning
confidence: 99%
“…The results indicate that the technological innovation has a significant positive effect on the business performance of Latin American family SMEs. In addition, (Akinwale et al , 2017) examined the impact of research and development (R&D) expenditure, product and process innovations on SMEs performance in the manufacturing industry in Nigeria using a survey of 1,000 SMEs. Their results with the least squares method showed that R&D spending by the firms as well as product and process innovation has significant impacts on the firm's performance.…”
Section: Innovation and Performance In Small And Medium Enterprises: A Literature Reviewmentioning
confidence: 99%
“…Therefore, innovation becomes an arrow that drives productivity in all sectors of the economy (Kim 2011). Innovation is traditionally viewed as taking place mostly within a single firm (Akinwale, Adepoju & Olomu 2017;Chesbrough 2003b). However, it has become a vital element in today's globalised and competitive environment (Mytelka 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of firms in developing countries, Nigeria in particular, are SMEs and are characterised by limited human and financial capabilities, their extent of adopting innovation to drive financial performance is not negligible (Adeyeye et al 2015). The level of in-house R&D capabilities and the extent of interactions of the knowledge institutions with some SMEs in the manufacturing and service sectors may generally be inadequate and low, yet these firms continue to strive to bolster their profits through innovations (Adeyeye, Jegede & Akinwale 2013;Akinwale et al 2017;Egbetokun, Adeniyi & Siyanbola 2012;Siyanbola et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Business organisations are looking for competitive advantage, and innovation creation or adoption at a firm-level provides an essential competitive advantage to the firm (Akinwale, Adepoju & Olomu, 2017). Innovation is the key to the progress of the business firm and critical to remain competitive.…”
Section: Introductionmentioning
confidence: 99%